THE ROLE OF INDIVIDUAL TRAINING IN THE DEVELOPMENT OF AUDITORY PERCEPTION (Web of Teachers: Inderscience Research, 2026)
This article reveals the role of individual training in the formation and development of auditory perception in children with hearing impairment. The effectiveness of individual training based on various methods and technologies, their impact on speech development, social adaptation and activity in the educational process are analyzed. According to the results of the study, an individual approach has been proven to be the most important factor in restoring auditory perception in accordance with the psychophysiological state and pace of development of each child.